The papers of Martin Luther King, Jr. - King, Martin Luther, Jr., 1929-1968.; Carson, Clayborne, 1944-; Luker, Ralph; Russell, Penny A. (Berkeley : University of California Press, 1992)
More than two decades after his death, Martin Luther King, Jr.'s ideas - his call for racial equality, his faith in the ultimate triumph of justice, and his insistence on the power of nonviolent struggle to bring about a major transformation of American society - are as vital and timely as ever. The wealth of his writings, both published and unpublished, that constitute his intellectual legacy are now preserved in this authoritative, chronologically arranged, multivolume edition. Faithfully transcribing the texts of his letters, speeches, sermons, student papers, and articles, this edition has no equal.
Volume II begins with King's doctoral work at Boston University and ends with his first year as pastor of the historic Dexter Avenue Baptist Church in Montgomery, Alabama. It includes papers from his graduate courses and a fully annotated text of his dissertation. There is correspondence with people King knew in his years before graduate school and a transcription of the first known recording of a King sermon. We learn, too, of King's marriage to Coretta Scott. Accepting the call to serve Dexter, King followed the church's tradition of socially active pastors by becoming involved in voter registration and other issues of social justice. In Montgomery he completed his doctoral work, and he and Coretta Scott began their married life. King's early papers document the formative experiences of a man whose life and teachings have had a profound influence not only on Americans but on people of all nations.
v. 1. Called to serve, January 1929-June 1951 --v. 2. Rediscovering precious values, July 1951-November 1955 -- v. 3. Birth of a new age, December 1955-December 1956 -- v. 4. Symbol of the movement, Jamuary 1957- December 1958.
Includes bibliographical references and index.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Archives; African Americans -- Civil rights; Civil rights movements -- United States -- History -- 20th century; United States -- Race relations